PENGARUH LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN DI WHIZ PRIME HOTEL PADANG - Mutia, Intan Luthfi (RC-INSTITUT, 2019)
The purpose of this research is to see the impact of working environment on the employees performance at Whiz Prime Hotel Padang. The study uses two variables: the work environment as the dependent variable (X) and the employee’s performance as the dependent variable (Y). This type of reaserch is a quantitative descriptive with causal approach of using a simple linear regression test. The population in this study was all the employees of Whiz Prime Hotel Padang which amounted to 32 people. The sample collection technique is using a saturated sample. Primary data collection techniques are conducted trough questionnaire (poll) which is based on the likert scale and has validity and reliability tests, secondary data using employee performance data at Whiz Prime Hotel Padang. The results of the study show: (1) The overall work environment is in excellent category (62.5%), (2) Employee performance is in excellent category (62.5%), (3) Work environment affects employee performance amounting to (37.1%).